Sign, function and life: Thinking epistemologically about biosemiotics - Toutain, Anne-Gaëlle (Sign Systems Studies, 2022)
This article focuses on an epistemological analysis, Bachelardian and Saussurean, of the problematics of biosemiotics. This discipline is first characterized in its general features, and in contrast with biolinguistics – a characterization that allows us to see its foundation on the traditional definition of the sign. Then, the Saussurean break with this traditional definition is explained, and with it the theorization which is constitutive of the Saussurean concept of language (la langue), explaining the given: the idioms. Biosemiotics appears in this “recurrent light” as a scientific ideology in the sense of Georges Canguilhem. It is a counterpart of structuralism, another scientific ideology, which emphasized the notion of structure, whereas this time it is the sound/sense relationship that is at the heart of the elaboration. Its commonality of problematics with and its singularity in relation to biolinguistics appear at the same time: if biolinguistics and biosemiotics both ignore the heterogeneity and the discontinuity constitutive of language, the reductionism of biosemiotics takes the form of a dissolution instead of the organicism underlying biolinguistics.